Treatment of Waldenstrom's macroglobulinemia resistant to standard therapy with 2-chlorodeoxyadenosine: Identification of prognostic factors - Dimopoulos, M.A.; Weber, D.; Delasalle, K.B.; Keating, M.; Alexanian, R. (Annals of Oncology, 1995)
Background: Few effective treatments are available for patients with Waldenstrom's macroglobulinemia that is resistant to standard therapies. We assessed the activity of 2-chlorodeoxyadenosine (2CdA) in patients with resistant macroglobulinemia in order to identify those most likely to benefit. Patients and methods: 2-chlorodeoxyadenosine was given to 46 consecutive patients with Waldenstrom's macroglobulinemia resistant to a combination of an alkylating agent and a glucocorticoid. Two courses were administered to outpatients at a dose of 0.1 mg/kg body weight per day for a 7-day continuous infusion using a portable pump through a central venous catheter. Responding patients were followed without further therapy. Results: Twenty of 46 patients responded to 2CdA therapy (43%; 95 CI; 29 to 60%) with a significantly higher frequency of benefit among patients with disease relapsing off therapy (78%) or with primary resistant disease within the first year (57%) than in those with later phases of disease (22%). The median survival after treatment was 28 months and the median progression-free survival of responding patients was 12 months. The longest survival was measured in patients with primary refractory disease (projected median 36 months) and the shortest in those with disease in refractory relapse (median 13 months). Conclusion: 2-Chlorodeoxyadenosine is active against macroglobulinemic lymphoma resistant to standard regimens and most effective in patients with disease relapsing off treatment or during the first year of primary refractory disease. Little benefit was observed among patients with later phases of resistant disease who should receive alternative treatments. © 1995 Kluwer Academic Publishers.
Keywords: 2-chlorodeoxyadenosine; Treatment; Waldenström's macroglobulinemia